Primary Langerhans cell histiocytosis of the vulva: Report of a case and brief review of the literature - Pan Zenggang; Sharma Sanjeev; Sharma Poonam (Wolters Kluwer Medknow Publications, 2009)
Primary Langerhans cell histiocytosis (LCH) of the vulva is rare. Fifteen cases of primary cutaneous vulvar LCH have been reported in English literature. We report an additional case of LCH confined to the vulva. In this article, we describe the clinical presentation, histopathology and immunohistochemistry findings of vulvar LCH that are helpful to both gynecologists and pathologists in the diagnosis of this entity. We briefly discuss the pathogenesis of LCH. The debate whether LCH is a reactive or neoplastic entity is still ongoing.